Earth and life through time - Stanley, Steven M. (New York : Freeman, 1986)
This integrated view of earth history has led me to write a text which can serve as self-contained introduction to both the biological and the geological aspects o four planet's evolution.
Part One. The environmental setting -- Part Two. The dimension of time -- Part three. Movements of the earth -- Part Four. The precambrian world -- Part five. The paleozoic era -- Part six. The mesozoic era -- Part seven. The cenozoic era.
Includes bibliographical references and index.
Keywords: HISTORICAL GEOLOGY